(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Complex Lanthanum nickelates were produced by the co-precipitation method with further heat-treating of the obtained batch. Researched the influence of Lanthanum nickelates composition on resistive qualities of the obtained samples. Studied the phase and chemical composition of the obtained complex oxide compounds and oxygen nonstoichiometry. It is demonstrated that Ni-based and La-based complex oxide systems related to Ruddlesden-Popper (RP) phase of total composition Lan+1NinO3n+1 (1≤n≤3) show anomalously high conductivity. For the system La2-xNiO4-d in the range 0,6≤x≤1 revealed metal character of conductivity-temperature dependence. For substituted RP phases La3-xMexNi2O7-δ and La4-xMexNi3O10-δ (Me=Ca, Sr, Ba) high conductivity belongs to the compounds in which ionic radius of substituent exceed ionic radius of Lanthanum in case of single-phase compound. When the number of substituents is increased for the listed above systems, transition takes place from metal conductivity to semi-conductivity and dielectric conductivity. Therefore, electric conductivity of oxide compounds with RP phase structure essentially depends on density of conduction electrons in unit cell. Change of conduction dependence may be also related to structural imperfection of the formed RP phases, and replacement of more conductive layers Lanthanum-Oxygen with less conductive layers alkaline-earth metals-oxygen. Increase of containing of trivalent Nickel leads to the increase of overlapping degree of dx2-y2 and рO2-orbital’s of ions in equatorial planes, and, correspondingly, decrease of energy barrier between conduction band and valence band. Because of that, the temperature of transition semiconductor-metal significantly decreases and electric conductance in chains -O2–Ni3+-O2–Ni2+-O2– increases. When content of trivalent Nickel in complex oxide is over 50%, Lanthanum nickelates demonstrate metal conduction type.